Character education in English subject: Teachers' perceptions and strategies - Aghni, Luluk Aulia; Vianty , Machdalena; Petrus, Ismail (Universitas Muhammadiyah Sidoarjo, 2020)
Character education is a purposeful, proactive attempt to develop good character in students or, more simply, to teach students about the right and the wrong. In relation to character education, the purposes of this study were to find out teachers’ perceptions on character education and their strategies to implement it in the classroom. In addition, this study also investigated the teachers’ problems in implementing character education and their proposed solution. The participants of this study were two teachers of English at one of public senior high school in Palembang and the students from two classes which taught by the two teachers. The data of this study were collected through questionnaire, interviews, classroom observation and document review. The result of this study showed that the teachers agreed that character education was important to be applied during teaching and learning program through the strategies such as group discussion or individual assignment. Students’ personal characters and behaviors stated by the teachers as the problem in teaching the character education and having a communication with students and observing them during teaching and learning process were mention as the ways to solve the problem.